RE1 silencing transcription factor/neuron‐restrictive silencing factor regulates expansion of adult mouse subventricular zone‐derived neural stem/progenitor cells in vitro. Issue 8 (17th February 2015) - Soldati, Chiara; Caramanica, Pasquale; Burney, Matthew J.; Toselli, Camilla; Bithell, Angela; Augusti‐Tocco, Gabriella; Stanton, Lawrence W.; Biagioni, Stefano; Buckley, Noel J.; Cacci, Emanuele
Abstract : Adult neural stem cell (aNSC) activity is tuned by external stimuli through the recruitment of transcription factors. This study examines the RE1 silencing transcription factor (REST) in neural stem/progenitor cells isolated from the subventricular zone of adult mouse brain and provides the first extensive characterization of REST‐mediated control of the cellular and molecular properties. This study shows that REST knockdown affects the capacity of progenitor cells to generate neurospheres, reduces cell proliferation, and triggers cell differentiation despite the presence of growth factors. Genome‐ and transcriptome‐wide analyses show that REST binding sites are significantly enriched in genes associated with synaptic transmission and nervous system development and function. Seeking candidate regulators of aNSC function, this study identifies a member of the bone morphogenetic protein (BMP) family, BMP6, the mRNA and protein of which increased after REST knockdown. The results of this study extend previous findings, demonstrating a reciprocal control of REST expression by BMPs. Administration of exogenous BMP6 inhibits aNSC proliferation and induces the expression of the astrocytic marker glial fibrillary acidic protein, highlighting its antimitogenic and prodifferentiative effects. This study suggests that BMP6 produced in a REST‐regulated manner together with other signals can contribute to regulation of NSC maintenance and fate. © 2015 Wiley Periodicals, Inc.